Mechanistic insights into HPV-positivity in non-smokers and HPV-negativity in smokers with head and neck cancer - Markus Hoffmann; Markus Hoffmann; Susanne Hille; Susanne Hille; Susanne Hille; Asita Fazel; Martin Laudien; Martin Laudien; Susanne Wiegand; Susanne Wiegand; Martin Müller; Oliver J. Müller; et al. (Frontiers in Oncology)
IntroductionSeveral aspects of the involvement of HPV in the pathogenesis of HPV-associated diseases remain poorly understood including mechanistic aspects of infection and the question of why the majority of HPV-positive HNSCC-patients are non-smokers, whereas HPV-negatives are smokers. Our previous research, based on 1,100 patient samples, hypothesized an explanation for this phenomenon: Smoking induces upregulation of a mucosal protective protein (SLPI), which competes with HPV for binding to Annexin A2 (AnxA2), pivotal for HPV cell entry. Here we investigate the mechanistic aspects of our hypothesis using transfection assays.MethodsHaCaT and HeLa cell lines were used to investigate the effects of shRNA transfection and nicotine exposure on HPV16-PsV-uptake. Cells were treated with Lipofectamine™ RNAiMAX for 48 or 72 hours with specific shRNA-concentrations, while nicotine was added to the cell medium at the indicated concentrations. Protein isolation, SLPI- and AnxA2-quantification, LDH cytotoxicity assessment, HPV16-PsV-uptake measurement, mRNA-isolation, cDNA-synthesis and RT-qPCR were performed.ResultsIn vitro transfection experiments with HPV16 pseudovirions (PsVs) showed that PsVs entered cells significantly better when SLPI was downregulated and significantly less when AnxA2 was downregulated. Nicotine exposure increased SLPI levels and reduced PsV uptake.ConclusionsThe overexpression of SLPI caused by tobacco-smoking can hinder HPV cell entry by binding to AnxA2 and thus prevent successful HPV infection. Conversely, non-smokers have lower SLPI-levels, associated with an excess of unbound AnxA2, favoring HPV cell-entry. These findings support our hypothesis, suggesting a paradigm shift in understanding virus-related pathogenesis, particularly in the head and neck region, and the nature of HPV infection.